Rural Adolescent Girls Negotiating Healthy and Unhealthy Romantic Relationships - Luft, Toupey; Jenkins, Melissa; Cameron, Catherine Ann (Canadian Journal of Counselling and Psychotherapy, 2012)
<span style="color: black; font-family: "AGaramondPro-Regular","serif"; font-size: 10pt; mso-bidi-font-family: AGaramondPro-Regular; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-CA; mso-fareast-language: EN-CA; mso-bidi-language: AR-SA;">The focused discussions of adolescent girls were analyzed to explore the processes of managing healthy and unhealthy aspects of dating relationships. Grounded theory methods were used to generate an outline of these processes. The core category elicited from discussions with participants was <span style="color: black; font-family: "AGaramondPro-Italic","serif"; font-size: 10pt; mso-bidi-font-family: AGaramondPro-Italic; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-CA; mso-fareast-language: EN-CA; mso-bidi-language: AR-SA; mso-bidi-font-size: 12.0pt;">wrestling with gender expectations<span style="color: black; font-family: "AGaramondPro-Regular","serif"; font-size: 10pt; mso-bidi-font-family: AGaramondPro-Regular; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-CA; mso-fareast-language: EN-CA; mso-bidi-language: AR-SA;">. This category reflected participants’ struggle to behave within the constraints they perceived that gender placed on their intimate relationships. Six subcategories explicated this core category: <span style="color: black; font-family: "AGaramondPro-Italic","serif"; font-size: 10pt; mso-bidi-font-family: AGaramondPro-Italic; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-CA; mso-fareast-language: EN-CA; mso-bidi-language: AR-SA; mso-bidi-font-size: 12.0pt;">determining<span style="color: black; font-family: "AGaramondPro-Regular","serif"; font-size: 10pt; mso-bidi-font-family: AGaramondPro-Regular; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-CA; mso-fareast-language: EN-CA; mso-bidi-language: AR-SA;"> <span style="color: black; font-family: "AGaramondPro-Italic","serif"; font-size: 10pt; mso-bidi-font-family: AGaramondPro-Italic; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-CA; mso-fareast-language: EN-CA; mso-bidi-language: AR-SA; mso-bidi-font-size: 12.0pt;">responsibility<span style="color: black; font-family: "AGaramondPro-Regular","serif"; font-size: 10pt; mso-bidi-font-family: AGaramondPro-Regular; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-CA; mso-fareast-language: EN-CA; mso-bidi-language: AR-SA;">, <span style="color: black; font-family: "AGaramondPro-Italic","serif"; font-size: 10pt; mso-bidi-font-family: AGaramondPro-Italic; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-CA; mso-fareast-language: EN-CA; mso-bidi-language: AR-SA; mso-bidi-font-size: 12.0pt;">keeping it in/letting it out, standing up for oneself, making sacrifices, building<span style="color: black; font-family: "AGaramondPro-Regular","serif"; font-size: 10pt; mso-bidi-font-family: AGaramondPro-Regular; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-CA; mso-fareast-language: EN-CA; mso-bidi-language: AR-SA;"> <span style="color: black; font-family: "AGaramondPro-Italic","serif"; font-size: 10pt; mso-bidi-font-family: AGaramondPro-Italic; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-CA; mso-fareast-language: EN-CA; mso-bidi-language: AR-SA; mso-bidi-font-size: 12.0pt;">trust/not trusting, <span style="color: black; font-family: "AGaramondPro-Regular","serif"; font-size: 10pt; mso-bidi-font-family: AGaramondPro-Regular; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-CA; mso-fareast-language: EN-CA; mso-bidi-language: AR-SA;">and <span style="color: black; font-family: "AGaramondPro-Italic","serif"; font-size: 10pt; mso-bidi-font-family: AGaramondPro-Italic; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-CA; mso-fareast-language: EN-CA; mso-bidi-language: AR-SA; mso-bidi-font-size: 12.0pt;">showing respect/showing disrespect. <span style="color: black; font-family: "AGaramondPro-Regular","serif"; font-size: 10pt; mso-bidi-font-family: AGaramondPro-Regular; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-CA; mso-fareast-language: EN-CA; mso-bidi-language: AR-SA;">Implications for psychotherapeutic work and educational applications are discussed.